Changes in forest ecosystem stability under climate change in a temperate landscape - Pavithra Rangani Wijenayake; Takuto Shitara; Akiko Hirata; Tetsuya Matsui; Tetsuya Matsui; Yasuhiro Kubota; Takashi Masaki (Frontiers in Forests and Global Change)
Climate change poses significant threats to forests globally. Understanding the relationship between environmental variables and species distribution is crucial for evaluating the vulnerability of tree species assemblies to anticipated climate change. Here, we address whether projected future changes in climate suitability are related to the structural stability of the old-growth forest community in Japan. We hypothesize that even with the expected changes in climate, the structural stability of the species assembly will remain unchanged until the end of this century. We modeled the influence of climate change on the spatial distribution of major tree species in a temperate deciduous forest reserve using local and regional presence data. We used the Maxent model and QGIS software to project potential habitat changes. Focusing on the period 2081–2,100, we used the MRI-ESM2-O general circulation model under baseline (SSP5–8.5) and mitigation (SSP1–2.6) future climate scenarios. This revealed that winter temperature is the most crucial factor affecting the distribution of tree species in the temperate landscape. Canopy tree species such as Acer pictum and Castanea crenata are projected to remain stable under SSP5–8.5 in 2100. Our results also suggest that the distribution of Quercus serrata, the dominant species in the forest studied, will expand, particularly under extreme climate conditions in 2100. However, there may be potential reductions in the abundance of subcanopy species, indicating a change in the structure of the forest stand. In this sense, the stability of forest ecosystems and local species diversity may be vulnerable under future climate change scenarios. Exploring the future species distribution and stand structure can improve understanding of habitat changes in temperate landscapes and requires more focused research efforts.